Speaking secrets of the masters : the personal techniques used by 22 of the world's top professional speakers - Speakers Roundtable (Mechanicsburg, PA : Executive Books/Life Management Services, Inc., 1995)
Professional speakers give their advice and personal techniques in the field of public speaking.
Keywords: Public speaking; Speeches, addresses, etc